Complete plastid genome of Primula calliantha Franch. (Primulaceae): an alpine ornamental plant endemic to Hengduan Mountain, China. Issue 9 (2nd September 2021) - Yang, Xuedan; Huang, Yuan; Li, Zhonghu; Chen, Jiahui
Abstract: Primula calliantha Franch. is an alpine species with an ornamental value that is endemic to the Hengduan Mountains of southwest China. Here, we sequenced and assembled its plastid complete genome, which is a circular molecule of 151, 954 bp and contains a large single-copy (83, 820 bp) and a small single-copy (17, 814 bp) region, separated by a pair of inverted repeats (25, 160 bp). There are 131 genes, 86 protein-coding, 37 tRNAs, and 8 rRNAs in the plastome, of which 114 genes, 80 CDSs, 30 tRNAs, and 4 rRNAs are unique, respectively. The P. calliantha plastid genome shows a high level of synteny with its close relatives, P. chionantha, P. purdomii, and P. woodwardii . Phylogenetic analysis based on 60 complete chloroplast genomes of Primulaceae confirmed its delimitation in Primula .